NERACA EKOLOGI PENAMBANGAN TIMAH DI PULAU BANGKA Studi Kasus Pengalihan Fungsi Lahan di Ekosistem Darat - Eddy Nurtjahya; Fournita Agustina; Wike Ayu Eka Putri (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
Unequal understanding among tin mining stake holders on trade regulation often triggered social conflict and therefore it was suggested to build political will especially among national, provincial, and regencial/municipal government levels. One important effort to bring out political will is presenting an independent and scientific study on comparision between socio-economic and environmental impact of tin mining. Purposive sampling was conducted to inconventional miners at reserved forest at Lubuk Kelik hamlet, pepper farmers at Silip village, and rubber farmers at Bencah village. Tin mining changed soil properties and microclimate, reduced vegetation composition and structure, arbuscular mycorrhizal fungi, phosphate solubilizing microorganism, ants, and Collembola population. Land conversion increased and contributed up to 95% income. The welfare improvement, however, was apparent as the recovery cost was neglected by inconventional tin miners, and only pepper land conversion showed benefit. Inconventional tin mining regulation needs improvement in order to increase land use efficiency and recovery cost. Understanding on ecological balance of more people and for more sustainable social welfare should be improved as well.